Praktik Bermusik Musisi Kota Solo: Modalitas, Profesionalisme, dan Kualitas Karya dalam Dinamika Kerja Musik - Nickelo Indira; Bondan Aji Manggala (Lembaga Pengembangan Kinerja Dosen, 2025)
Musical modality, professionalism, and work quality in everyday musical practice constitute the main analytical framework of this study. This research departs from the view that musical professions are often reduced to hobby-based activities, whereas in practice they involve work strategies, professional attitudes, and negotiation between artistic idealism and market demands. This study employs a qualitative approach through in-depth interviews with two musicians in the city of Solo, Aditya Ong and Indra Permana, who represent different backgrounds, professional roles, and musical orientations. The findings indicate that modality comprising experience, musical skills, and professional networks forms the foundation of musicians’ professionalism. Professionalism is reflected not only in technical competence, but also in work ethics, responsibility, and the ability to position oneself within various musical work contexts. Work quality is not understood normatively as good or bad, but as the outcome of how musicians manage their modality and professionalism in specific working situations. This study concludes that musical practice in Solo is shaped through continuous negotiation between artistic orientation, market demands, and the pursuit of livelihood stability. Musical modality, professionalism, and work quality are interconnected in forming musicians’ strategies to sustain their musical practices amid the dynamics of the local music industry.